Construction of Power Automatic Control System Based on Interval Optimization Algorithm - Xie, Hongkai; Jiang, Weicheng; Wang, Chunsheng (2024 International Conference on Data Science and Network Security (ICDSNS), 2024)
With the continuous development and growth of the power control system, the staff's requirements for the stability and energy utilization of the system have also become higher. In order to meet these needs, this paper proposes a new system based on interval optimization algorithm. By defining the goals of the power system monitoring and control system, and using sensors to collect data, the interval optimization algorithm is successfully integrated into the system to realize the practical application of optimization results and continuously monitor the performance and operation of the system. This method represents the parameters as intervals, considers the uncertainty and variability of the parameters, and uses global optimization and multi-objective optimization techniques to find the optimal solution. The experimental results show that the stability of the system in this paper is between 90% and 98%, and the power automatic control system based on the interval optimization algorithm has achieved significant improvements in stability and energy utilization efficiency.